The Role of Financial Inclusion Mediation and Technological Innovation in The Relationship Between CEO (Chief Executive Officer) Financial Literacy and Msme Performance - Kalya Meidina; Gregorius Jeandry; Asrudin Hormati (Journal of International Conference Proceedings, 2025)
This study examines the influence of CEO financial literacy on the performance of Micro, Small, and Medium Enterprises (MSMEs) by analyzing the mediating roles of financial inclusion and technological innovation. The research is motivated by the limited empirical evidence on how managerial financial competence affects MSME competitiveness in developing economies such as Indonesia. Using a quantitative approach, data were collected through structured questionnaires distributed to 100 MSME CEOs in Ternate and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) technique. The results indicate that CEO financial literacy has a positive and significant impact on MSME performance. However, financial inclusion was found to be an insignificant mediator, suggesting that access to financial services has not been optimally utilized for productive activities. In contrast, technological innovation significantly mediates the relationship between CEO financial literacy and MSME performance, demonstrating that financially literate CEOs are more likely to adopt digital technologies that enhance efficiency and competitiveness. The findings underscore the strategic importance of strengthening financial literacy and digital transformation among MSMEs to sustain long-term growth and resilience